Plan de marketing para mejorar el posicionamiento competitivo de la empresa visualNET en el cantón Simón Bolívar durante 2024, mediante estrategias para captar y fidelizar clientes. - Santos Pita, Ramon Héctor (2025)
The main objective of this research project is to improve the competitive positioning of VisualNET, a company located in the Simón Bolívar canton, through the implementation of digital marketing strategies and loyalty programs. The identified problem is the lack of digital visibility and the need to strengthen the relationship with current and potential customers. To address this challenge, a quantitative methodology is employed, using surveys, interviews, and secondary data analysis to evaluate customer perception and the effectiveness of digital marketing strategies. The expected result is an improvement in the company's digital positioning, an increase in its customer base, enhanced customer satisfaction and loyalty, and a positive return on investment (ROI). The implementation of SEO strategies, social media marketing, and loyalty programs such as discounts and reward systems will contribute to strengthening VisualNET's digital presence. In conclusion, the proposal is expected to drive the company's sustainable growth, enhancing its competitiveness in the local market. Continuous evaluation of strategies will allow for adjustments based on results, ensuring long-term success.